IMPORTANCE OF PHYSICOCHEMICAL EVALUATION AND MICROBIOLOGICAL ANALYSIS IN ARTESIAN WELLS - Valger Coli, Ricardo; Henrique De Jesus Cardoso, Luiz; Henrique Bolkart Holz, Guilherme; Karolini Walger Schultz, Leticia (Journal of Interdisciplinary Debates, 2022)
The use of water as a natural resource is essential for the existence of life on the planet, and a recurring theme in various spaces of discussion and investigation, due to the concern of all social spheres. Water resources and related ecosystems are related to water resources, sustainable use of water changes and climate change. A worldwide source with a view to large use, due to its global form, it is guaranteed to verify the patterns of use by the large capacity, not considering that they can be presented by the large amount of water predicted9. 2011, in addition to the ability to transmit pathogens presents in the feces. There are several methods for the analysis of bacteria of the coliform group and Escherichia coli, among them the organisms are of the Most Probable Number, in which a technical estimate is made of how many are present in the original sample. This method is done through a series of serial dilutions, using the inverted Durhan tube to analyze the presence of microorganisms and the bright green broth 2% lactose bile to confirm the presence of total and thermotolerant coliforms. After the sample sampling period, the calculation of how many microorganisms that were analyzed are present in the sample is made. The present reviews data on water use, consumption and distribution, use of the most likely number method and its application to the analysis of water from artesian wells. With an increase in the need for education and an increase in the need to increase the number of equipment, in addition to the need to increase the amount of information, and not to increase the need to increase the number of equipment needed, in addition to the need to increase the amount of information and not to increase the need to increase the number of equipment needed.